التدريب والتعلم المستمران للكفاءات وأثرهما على الميزة التنافسية *دراسة حالة مجمع صيدال - مرزوقي, ياسر; بن ديب, عبد الرشيد (University of Eloued جامعة الوادي, 2018)
يهدف هذا البحث إلى معرفة الدور الذي يلعبه التدريب والتعلم المستمرين للكفاءات في تحقيق التفوق التنافسي للمنتجات الدوائية بمجمع صيدال، ولتحقيق هدف الدراسة قام الباحث بتصميم استبيان شمل (28) فقرة لجمع البيانات الأولية من عينة البحث المكونة من (169) مستجوب، وفي ضوء ذلك تم جمع وتحليل البيانات واختبار الفرضيات باستخدام برنامج (spss)، وبعد إجراء عملية التحليل لبيانات البحث وفرضياته تم التوصل إلى مجموعة من الاستنتاجات أهمها؛ هناك دور كبير للتدريب في تحسين أداء الكفاءات، الذي بدوره يسهم في تعزيز الميزة التنافسية للمنظمة من خلال ما أظهرته نتائج التحليل التي تؤكد أن هناك علاقات ارتباط قوية بين (التدريب والتعلم المستمران للكفاءات) و(الميزة التنافسية للمنتجات الدوائية لمجمع صيدال). Abstract: This study examines the role played by training and competency development in enhancing the competitive advantage of pharmaceutical products at the Sidal Complex. To achieve this, the study used a questionnaire consisting of 28 items to collect preliminary data from the sample of 169 researchers. The research hypotheses were formulated based on the collected data and tested using SPSS. This resulted in several conclusions. Most importantly, training plays a significant role in improving competency performance, which in turn contributes to enhancing the competitive advantage of the organisation. Hence, the paper concludes that there is a strong correlation between the development of competencies and competitive advantage
Continuous training and learning of competencies and their impact on achieving competitive advantage - Sidal Complex Case Study -
مجلة رؤى المجلد الثامن العدد الثاني
Keywords: تدريب ; تعلم مستمر ; كفاءات ; ميزة تنافسية; Training, Continuous Learning, Competencies, Competitive Advantage Jel Classification Codes : O320; C120 ; C220